Combination of Progressive Muscle Relaxation - Lavender Aromatherapy in Improving Sleep Quality in Menopausal Women: A Quasy Experiment - Mustofa, Muhammad; Japaries, Willie; Desma Ayu Kusuma Wardani, Frisca; Maris Bakara, Stella; Suminah (Chakra Brahmanda Lentera Institute, 2024)
Background: Menopausal women often experience emotional disorders such as anxiety, irritability, and depression, as well as physical problems such as pain during intercourse, hot flushes, and sleep disturbances. Poor sleep quality is a major complaint during menopause. This study aims to analyze the effect of the combination of Progressive Muscle Relaxation (PMR) and lavender aromatherapy on the sleep quality of menopausal women. Methods: This quasi-experimental research uses a pretest-posttest approach with purposive sampling, involving 20 menopausal female respondents at the Posyandu Elderly in Belangwetan Village, North Klaten, from July 14 to 29, 2024. The intervention given was a combination of PMR, which involves tensing and relaxing the muscles for 15-20 minutes a day, while inhaling lavender aromatherapy. Result: Before the intervention, the average sleep quality of the respondents was 17.25 (range 13-20), which decreased to 5.90 (range 4-9) after the intervention. The Wilcoxon test showed a p-value = 0.000, proving that this intervention was effective in improving sleep quality in menopausal women. Conclusion: The combination of PMR and lavender aromatherapy is effective in improving sleep quality because it helps relax muscles, activates the body's relaxation system, and is easy to apply.